2018
DOI: 10.1007/s00181-018-1581-x
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying role of macroeconomic shocks on house prices in the US and UK: evidence from over 150 years of data

Abstract: In this paper, we study the effect of macroeconomic shocks in the determination of house prices. Focusing on the U.S. and the U.K. housing market, we employ timevarying Vector Autoregression models using Bayesian methods covering the periods of 1830-2016 and 1845-2016 respectively. We consider real house prices, output growth, short-term interest rates and inflation as input variables in order to unveil the effect of macroeconomic shocks on house prices. From the examination of the impulse responses of house p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…While there exists a large number of studies that have analyzed the role of both conventional and unconventional (in the wake of the zero lower bound (ZLB) scenario) monetary policy [3][4][5][6][7][8], and more recently, fiscal policy shocks on real estate markets [9,10], and the feedback from it in shaping policy decisions, there is dearth of studies that have analyzed the role of aggregate demand, aggregate supply, and bond yield spread shocks on real estate markets. The only exception to this is the recent paper by Plakandaras et al [11], where the authors study the effect of macroeconomic shocks in the determination of house prices in the US and the UK by employing time-varying parameter vector autoregressive (TVP-VAR) models covering the historical annual periods of 1830 to 2016 and 1845 to 2016, respectively. From the examination of the impulse responses of house prices on macroeconomic shocks, Plakandaras et al [11], found that technology shocks dominate in the U.S. real estate market, while their effect is unimportant in the U.K, where, monetary policy shocks drives most of the house price evolution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…While there exists a large number of studies that have analyzed the role of both conventional and unconventional (in the wake of the zero lower bound (ZLB) scenario) monetary policy [3][4][5][6][7][8], and more recently, fiscal policy shocks on real estate markets [9,10], and the feedback from it in shaping policy decisions, there is dearth of studies that have analyzed the role of aggregate demand, aggregate supply, and bond yield spread shocks on real estate markets. The only exception to this is the recent paper by Plakandaras et al [11], where the authors study the effect of macroeconomic shocks in the determination of house prices in the US and the UK by employing time-varying parameter vector autoregressive (TVP-VAR) models covering the historical annual periods of 1830 to 2016 and 1845 to 2016, respectively. From the examination of the impulse responses of house prices on macroeconomic shocks, Plakandaras et al [11], found that technology shocks dominate in the U.S. real estate market, while their effect is unimportant in the U.K, where, monetary policy shocks drives most of the house price evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The only exception to this is the recent paper by Plakandaras et al [11], where the authors study the effect of macroeconomic shocks in the determination of house prices in the US and the UK by employing time-varying parameter vector autoregressive (TVP-VAR) models covering the historical annual periods of 1830 to 2016 and 1845 to 2016, respectively. From the examination of the impulse responses of house prices on macroeconomic shocks, Plakandaras et al [11], found that technology shocks dominate in the U.S. real estate market, while their effect is unimportant in the U.K, where, monetary policy shocks drives most of the house price evolution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The root of the global economic and financial crisis of 2008-2009 is commonly associated with the rapid decline in real estate prices, following a prolonged boom. Since there exists a large literature on the impact of monetary policy on general real estate prices and vice versa (see for example, Del Negro and Otrok (2007), Bjørnland and Jacobsen (2010), Bjørnland and Jacobsen (2013), Rahal (2016), Simo-Kengne, Miller, Gupta, and Balcilar (2016), Marfatia, Gupta, and Cakan (2017)), Huber and Punzi (2018), Plakandaras, Gupta, Katrakilidis, and Wohar (2018), it is not surprising that there is now a revived interest in the long standing debate on whether and how monetary policy should respond to perceived deviations of real prices from fundamentals. Given the beliefs that asset price bubbles are difficult to detect and measure, and that interest rates are a blunt instrument to prick a bubble resulting in unintended collateral damages, the consensus view is that central banks should focus on stabilizing inflation and the output gap only (Bernanke and Gertler (1999); Bernanke and Gertler (2001); Kohn (2006)).…”
Section: Introductionmentioning
confidence: 99%